L'esperienza modernista in eco al pensiero dell'Ereignis: Arte e politica in E. E. Cummings. Parte I: Il ritmo del senso (Itinera, 2024)
The imminent completion of the publication of Martin Heidegger’s Gesamtausgabe will allow scholars to deepen the meaning of the relationship between thought and art and, simultaneously, the nature of the instance that presides over both these cognitive manifestations. In particular, the analysis of the phenomenon of Enowning will promote the understanding of the intimate meaning of Edward Estlin Cummings’ poetic work and the scope of the parallel path followed by the poet within the pictorial experience he undertook based on the figurative revolutions inaugurated by Paul Cézanne and Cubism. The pictorial search for a space that is not reduced to representing objects but provides the place where they can instead make their appearance establishes the dimension that grants man a time to be one with everything. Correspondingly, the poetic word becomes capable of naming the phenomenon of the self-concealment of Being and becoming the guardian of the possibility of all that is.